Talking at the table: Preaching on Communion Sunday. (August 2019) - Graves, Mike
Although the historic pattern of Christian worship features the sermon and Communion, coming out of the Reformation many traditions observe Communion only occasionally. In both cases, the relation of the two is not apparent. The article considers what preachers as well as liturgists might consider when both sermon and Communion occur.